Mitochondrial DNA point mutations and relative copy number in 1363 disease and control human brains - Wei, Wei; Keogh, Michael J.; Wilson, Ian; Coxhead, Jonathan; Ryan, Sarah; Rollinson, Sara; Griffin, Helen; Kurzawa-Akanbi, Marzena; Santibanez-Koref, Mauro; Talbot, Kevin; Turner, Martin R.; McKenzie, Chris-Anne; et al. (Acta neuropathologica communications, 2017)
Mitochondria play a key role in common neurodegenerative diseases and contain their own genome: mtDNA. Common inherited polymorphic variants of mtDNA have been associated with several neurodegenerative diseases, and somatic deletions of mtDNA have been found in affected brain regions. However, there are conflicting reports describing the role of rare inherited variants and somatic point mutations in neurodegenerative disorders, and recent evidence also implicates mtDNA levels. To address these issues we studied 1363 post mortem human brains with a histopathological diagnosis of Parkinson’s disease (PD), Alzheimer’s disease (AD), Frontotemporal dementia – Amyotrophic Lateral Sclerosis (FTD-ALS), Creutzfeldt Jacob disease (CJD), and healthy controls. We obtained high-depth whole mitochondrial genome sequences using off target reads from whole exome sequencing to determine the association of mtDNA variation with the development and progression of disease, and to better understand the development of mtDNA mutations and copy number in the aging brain. With this approach, we found a surprisingly high frequency of heteroplasmic mtDNA variants in 32.3% of subjects. However, we found no evidence of an association between rare inherited variants of mtDNA or mtDNA heteroplasmy and disease. In contrast, we observed a reduction in the amount of mtDNA copy in both AD and CJD. Based on these findings, single nucleotide variants of mtDNA are unlikely to play a major role in the pathogenesis of these neurodegenerative diseases, but mtDNA levels merit further investigation.